Price Of Sales PT Fanos Asia Unit Pringswu Lampung - Nur Aprilia Ningsih; Wagiyo; Arum Arumpi Kusnidar (Institute of Computer Science (IOCS), 2022)
Pricing is a company's strategy to make a profit, mistakes in pricing can cause losses, and pricing also depends on the company's status as a distributor, agent, or retailer. The calculation of the Cost of Cost carried out by PT Fanos Asia Unit Pringsewu Lampung does not include a component of equipment depreciation costs, while the company is not a distributor but mostly sells in retail. This study uses a quantitative descriptive method with data collection techniques in the form of documentation and interviews. The results showed (1) there was an increase in office overhead costs, which was caused by the imposition of depreciation costs, the office overhead costs per pcs, the cost of goods sold increased, so that the profit percentage decreased, if the expected profit remains, then the selling price must be increased, (2) Determination of the selling price of the cost plus pricing method can set a more efficient selling price. So that the price set by the company can be increased, (3) there is a difference in the amount of the selling price due to the different methods used.